How safe are children with COVID-19 from cardiac risks? Pediatric risk assesment; insights from echocardiography and electrocardiography - ŞAYLAN ÇEVİK, BERNA; KEPENEKLİ KADAYİFCİ, EDA; YAKUT, NURHAYAT; GÜNAL, ÖZGE (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Background/aim: Approximately 40 million individuals worldwide have been infected with SARS-CoV-2, the virus responsible for the novel coronavirus disease-2019 (COVID-19). Despite the current literature about the cardiac effects of COVID-19 in children, more information is required. We aimed to determine both cardiovascular and arrhythmia assessment via electrocardiographic and echocardiographic parameters. Materials and methods: We evaluated seventy children who were hospitalized with COVID-19 infections and seventy children as normal control group through laboratory findings, electrocardiography (ECG), and transthoracic echocardiography (TTE). Results: We observed significantly increased levels of Tp-Te, Tp-Te/QT, and Tp-Te/QTc compared with the control group. Twenty-five of 70 (35.7%) patients had fragmented QRS (fQRS) without increased troponin levels. On the other hand, none of the patients had pathologic corrected QT(QTc) prolongation during the illness or its treatment. On TTE, 20 patients had mild mitral insufficiency, among whom only five had systolic dysfunction (ejection fraction < 55%). There was no significant difference between the patient and control groups, except for isovolumic relaxation time (IVRT) in terms of mean systolic and diastolic function parameters. IVRT of COVID patients was significantly lower than that of control group. Conclusion: Despite all the adult studies, the effects of COVID (R) 19 on myocardial function are not well established in children. The thought that children are less affected by the illness may be a misconception.
Keywords: Children; COVID-19; electrocardiography; risk; TP-E/QT RATIO; ACUTE RESPIRATORY SYNDROME; KAWASAKI-DISEASE; FRAGMENTED QRS; INTERVAL; DISPERSION; MORTALITY